Evaluation of Vitamin D-levels and Bone Mineral Density in Lymphoma and Solid Tumors of Childhood after Treatment - Ozge Artan; Suna Emir (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2021)
As the survival rate of childhood cancers increases, late effects of the treatment are becoming significantly more critical. The aim of this study is to evaluate serum 25 Hydroxy Vitamin D levels and bone mineral density (BMD) of patients with lymphoma and solid tumors. In this study, we included patients diagnosed with cancer in our pediatric oncology department between 2004 and 2013. These patients were all in remission and completed their treatment. Patient data were collected from corresponding medical files. Vitamin D levels, BMD measurements and other laboratory tests were performed prospectively. The study group consisted of 105 patients who completed treatment at least one year ago. Overall, 59.6 % of the subjects were found to have vitamin D levels less than 20 ng/mL. When the factors affecting vitamin D deficiency were evaluated, there were not any factor related to vitamin D deficiency. However, a positive correlation was observed in the blood sampling time, namely test results taken in summer months (April-September) were higher. In our study, bone mineralization disorder (low BMD) was found in 44.4% of the patients. In addition, we observed that bone health was significantly affected in children who recovered from cancer. 59.6 % of the vitamin D deficiency rate was found to be higher than the similar age group in our country. To our knowledge, this is also the lowest vitamin D levels in children with cancer compared to previously published studies. The rate of low BMD was determined as 44.4%, similar to earlier studies.